Forecasting national medal totals at the Summer Olympic Games reconsidered - Scelles, N.; Andreff, W.; Bonnal, L.; Andreff, M.; Favard, P. (Social Science Quarterly, 2020)
This work was funded by the French Observatory of the Sports Economy, French Ministry for Sports. The authors would like to thank the French Observatory of the Sports Economy, French Ministry for Sports for having funded this research. They also want to thank the participants of the 11th Conference of the European Sport Economics Association in Gijon, Spain, for their feedback on the presentation of the article. In particular, they thank Prof. David Forrest and Dr. Juan de Dios Tena for their feedback on the full article. The authors also want to thank the editors and the referee for their very helpful comments. Errors are their own.